Ideological Composition of Economic Programs of CPRF (Communist Party), "Apple" and "Unity" - НовиковаЕлена Геннадиевна (Journal of Economic Sociology, 2010)
The paper includes the results of the analysis of the economic programs of political parties focusing on their ideology. The «ideal» typology of four ideological systems: Conservatism, Liberalism, Democratism and Socialism, was taken as an analytical instrument. This typology helped to analyze the economic programs of CPRF, «Apple» and «Unity». It was showed that the ideologies were reproduced as principle hybrids at the program level, based on interaction and intersection of the various «pure» ideologies. Moreover the author disclosed the special techniques, which allowed combining the principles of competing ideologies within one program without obvious contradictions. The final part of the paper is aimed at the discussion of the differences in ideological and lexical contents of the programs.